Structure Activity Relationship of N-Substituted Phenyldihydropyrazolones Against Trypanosoma cruzi Amastigotes - Sijm, Maarten; Maes, Louis; de Esch, Iwan J. P.; Caljon, Guy; Sterk, Geert Jan; Leurs, Rob (Frontiers in Chemistry, 2021)
Current drugs for Chagas disease have long treatment regimens with occurrence of adverse drug effects leading to poor treatment compliance. Novel and efficacious medications are therefore highly needed. We previously reported on the discovery of NPD-0227 (2-isopropyl-5-(4-methoxy-3-(pyridin-3-yl)phenyl)-4,4-dimethyl-2,4-dihydro-3H-pyrazol-3-one) as a potent in vitro inhibitor of Trypanosoma cruzi (pIC50 = 6.4) with 100-fold selectivity over human MRC-5 cells. The present work describes a SAR study on the exploration of substituents on the phenylpyrazolone nitrogen. Modifications were either done directly onto this pyrazolone nitrogen or alternatively by introducing a piperidine linker. Attention was pointed towards the selection of substituents with a cLogP preferably below NPD-0227’s cLogP of 3.5. Generally the more apolar compounds showed better activities then molecules with cLogPs < 2.0. Several new compounds were identified with potencies that are in the same range as NPD-0227 (pIC50 = 6.4) and promising selectivities. While the potency could not be improved, valuable SAR was obtained. Furthermore the introduction of a piperidine linker offers new opportunities for derivatization as valuable novel starting points for future T. cruzi drug discovery.